Perancangan Sistem Informasi Penjualan dan Persediaan Barang pada Toko Plastik Charles Jaya - Gunawan, Jenifer; Michael, Michael; Richi, Michael; Farisi, Ahmad (MDP Student Conference, 2025)
This research aims to develop a web-based information system for sales and inventory management that enhances the efficiency of transaction recording and stock management. The scope of the study includes key features such as user login, a dashboard, inventory management, sales transaction recording, and financial report generation. The methodology employed in this research encompasses system requirements analysis, design, implementation, and feature testing. The findings indicate that the developed system significantly improves the accuracy of transaction records, accelerates stock management processes, and simplifies the generation of financial reports compared to previous manual methods. The conclusion drawn from this research highlights that the implementation of this system contributes to increased operational efficiency within the business. However, there remains potential for further development, particularly regarding integration with external systems and enhancing data security.